Exploration of the decontamination of common nonmetallic materials by Ce(IV)/HNO3 - Jianzhu Pan; Jiaxiang Long; Guangnai Ma; Sheng Li (PLoS ONE, 2025)
With the rapid development of the nuclear medicine business worldwide, the removal of iodine-131 from specific contaminated environments to protect public health has important application prospects. In this study, the surface decontamination mechanism of Ce(IV)/HNO3 as a decontaminant for iodine-131-contaminated nonmetallic materials was investigated by using an orthogonal experimental method and scanning electron microscopy (SEM). During the preparation experiments with the contaminated materials, both quartz glass and ceramics reached peak activity concentration levels at 4 h of adsorption (contamination) by using immersion; the decontamination factor (DF) was selected as the test index for the decontamination experiments. The influence order of temperature, Ce(IV) concentration, HNO3 concentration and decontamination time on the decontamination factor (DF) was investigated with an orthogonal test and extreme difference analysis. The optimal combination of factors under the set experimental conditions was obtained after a comprehensive analysis. The optimal combination for quartz glass was a decontamination time of 2.0 h>temperature of 60°C > Ce(IV) concentration of 0.02 mol/L > HNO3 concentration of 1.5 mol/L; the optimal combination for the ceramic sheet was a Ce (IV) concentration of 0.02 mol/L>temperature of 80°C >decontamination time of 1 h > HNO3 concentration of 2.0 mol/L. Additionally, from the SEM analysis, the material surface decontamination process removed the surface iodine-131 and the highly accumulated organic substances; overall, a better decontamination effect was achieved.